Linear response function approach for the boundary problem of QM/MM methods. Issue 3 (7th May 2012) - Ueda, Koki; Yamanaka, Shusuke; Nakata, Kazuto; Ehara, Masahiro; Okumura, Mitsutaka; Yamaguchi, Kizashi; Nakamura, Haruki; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract We present a simple approach to treat the boundary problem in quantum mechanics and molecular mechanical (QM/MM) methods. The method is based on ab initio calculations of linear response functions, which indicate nonlocal polarization of densities due to the perturbations at the specific site. We describe basic ideas as well as some numerical results. The computational results will be discussed with the boundary problem in QM/MM methods. © 2012 Wiley Periodicals, Inc.